2011
DOI: 10.1037/a0023224
|View full text |Cite
|
Sign up to set email alerts
|

Choke or thrive? The relation between salivary cortisol and math performance depends on individual differences in working memory and math-anxiety.

Abstract: In the current study, we explored how a person's physiological arousal relates to their performance in a challenging math situation as a function of individual differences in working memory (WM) capacity and math-anxiety. Participants completed demanding math problems before and after which salivary cortisol, an index of arousal, was measured. The performance of lower WM individuals did not depend on cortisol concentration or math-anxiety. For higher WM individuals high in math-anxiety, the higher their concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 33 publications
6
87
1
3
Order By: Relevance
“…All participants completed the same eight modular arithmetic problems under time pressure as in the pilot study (Beilock et al, 2004;Mattarella-Micke et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants completed the same eight modular arithmetic problems under time pressure as in the pilot study (Beilock et al, 2004;Mattarella-Micke et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Time pressure, loss framing, social evaluation, and the phrase ''IQ test" have been shown to make people anxious (Beilock, 2008;Beilock & Carr, 2005;Beilock et al, 2004;Brooks, 2014;Ramirez & Beilock, 2011). After reading the task description (Low Anxiety or High Anxiety), participants completed the math task, a series of eight modular arithmetic math problems adapted from Mattarella-Micke, Mateo, Kozak, Foster, and Beilock (2011). Each question followed the same format using invented symbols.…”
Section: Math Task Pilot Studymentioning
confidence: 99%
“…Some studies have shown increased cortisol responses, related to stress, during performance on math tasks (Mattarella-Micke, Mateo, Kozak, Foster, & Beilock, 2011). Lyons and Beilock (2010) found that even thoughts of doing math elicited a negative emotional response from math anxious students.…”
Section: Interactivity Defuses the Impact Of Math Anxiety In Primary mentioning
confidence: 99%
“…The "IQ test" was actually a series of eight modular arithmetic math problems adapted from Mattarella-Micke, Mateo, Kozak, Foster, and Beilock (2011). Each question followed the same format using invented symbols.…”
Section: Methodsmentioning
confidence: 99%